2004
DOI: 10.1046/j.1365-3156.2003.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble transferrin receptor in Aboriginal children with a high prevalence of iron deficiency and infection

Abstract: Summaryobjectives Aboriginal children in tropical Australia have a high prevalence of both iron deficiency and acute infections, making it difficult to differentiate their relative contributions to anaemia. The aims of this study were to compare soluble transferrin receptor with ferritin in iron deficiency anaemia (IDA), and to examine how best to distinguish the effect of iron deficiency from infection on anaemia.methods We conducted a prospective study of 228 admissions to Royal Darwin Hospital in children f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In section 5.1, there were more Aboriginal young people reporting inadequate diets. Previous studies have shown iron deficiency in young people from Aboriginal communities, and this was shown to be related to inadequate consumption of dietary iron (Ritchie et al, 2004). One quarter of young people had ferritin levels below normal (25%), and there were more than twice as many Aboriginal as non-Aboriginal young people with low ferritin (35% vs 15%, p<0.001); this reflects the results for iron levels described above.…”
Section: Iron and Lipidssupporting
confidence: 73%
“…In section 5.1, there were more Aboriginal young people reporting inadequate diets. Previous studies have shown iron deficiency in young people from Aboriginal communities, and this was shown to be related to inadequate consumption of dietary iron (Ritchie et al, 2004). One quarter of young people had ferritin levels below normal (25%), and there were more than twice as many Aboriginal as non-Aboriginal young people with low ferritin (35% vs 15%, p<0.001); this reflects the results for iron levels described above.…”
Section: Iron and Lipidssupporting
confidence: 73%
“…because of prematurity, low birthweight, dietary risk factors and/or low socio‐economic status) at 1 year of age . The implementation and feasibility of these recommendations has been scrutinised by several papers, and they are currently only used in high‐prevalence populations such as Aboriginal and Torres Strait Islander infants …”
Section: Diagnosis Of Iron Depletion Iron Deficiency and Iron Deficimentioning
confidence: 99%
“…Erythrocyte indices such as hypochromicity, microcytosis and reticulocyte count offer more practical investigations with treatment (Grant 2007). Soluble transferrin receptor levels may improve the diagnosis of anaemia in settings with high burdens of infectious diseases and iron deficiency (Richie 2004). Alternatively, an increase in haemoglobin of more than 10 g/L after one-month treatment with 3 mg/kg/day of elemental iron is indicative of iron deficiency (Oski 1993).…”
Section: Description Of the Interventionmentioning
confidence: 99%